A contribuição dos processos de aprendizagem para acumulação de competências: trajetória de duas indústrias do segmento madeireiro do estado do Paraná - Holanda, Lucyanno Moreira Cardoso de (2010)
This study aims to identify how the learning processes contribute to the accumulation of skills in the technological functions of process and organization of production, product and equipment in two industries (ALFA and BETA) of the wood industry of Paraná, in the period of 1999 to 2008. To achieve this goal, the competence and learning models from Figueiredo (2001) are used. The competence model is analytical and matrix composed of columns and rows. The columns of the matrix structure represent the technological capability by function, and the lines show the degree of difficulty. In this structure there is also a routine and innovative competence division. The learning model is composed by four phases: the external and internal acquisition process, socialization and codification of knowledge and follow four features: variety, intensity, functioning and interaction. The scientific method used in this study was inductive, as the research is classified as applied, qualitative, exploratory and by survey. The population is composed of six directors (three from Alfa and three from Beta), who run the departments of Production, Products and Equipment and the sample is equal to the population. The instrument used in data collection was a questionnaire consisting of closed and open questions. Closed questions are related to the learning processes and open questions are related to the identification of skills. Regarding the results of the research it was possible to identify that in the ALFA and BETA industry the learning processes generated innovative capabilities in the three functions studied, butin distinct moments Given this information we can infer that the more learning processes are aggregated, and used continuously, with excellent performances and strong interaction the better and faster will be the accumulation of expertise.